Mysterious Artist with a Movie Camera - Александр Риганов:«Тиссэ. Оператор Эйзенштейна», Санкт-Петербург: Издательство «Сеанс»,2020. ISBN 978-5-6042795-1-9, 384 pp. - Debreceni, Ferenc (Slavica, 2022)
This review is a content and critical review of Alexander Riganov’s book on Soviet cinematographer Eduard Tisse (1897-1961), Tisse: Eisenstein’s cameraman, which was the first monograph of its kind published in Russian. The book follows the life of the first Soviet cameraman in chronological order from birth until his last days, with the author overviewingrelevant historic and cinematographic events throughout. Thus, there are three major stories in Riganov’s book: the life and artistic path of an artist, the history of a country, and the golden age of cinematography. Several unique archival documents, e.g. letters, diary segments, photographs etc., were first published in this book. The book’s author paid special attention to Tisse’s and Eisenstein’s joint works. The uniqueness and high professional standard of Riganov’s book makes it a piece of art worthy of attention.